Handbook of Clinical Child Neuropsychology - Reynolds, Cecil R.; Fletcher-Janzen, Elaine (Springer US : Imprint: Springer, 2009)
Handbook of Clinical Child Neuropsychology Third Edition Edited by Cecil R. Reynolds, Texas A&M University Elaine Fletcher-Janzen, University of Northern Colorado The past decade has brought important advances in our understanding of the brain, particularly its influence on the behavior, emotions, and personality of children and adolescents. In the tradition of its predecessors, the third edition of the Handbook of Clinical Child Neuropsychology enhances this understanding by emphasizing current best practice, up-to-date science, and emerging theoretical trends for a comprehensive review of the field. Along with the Handbook's impressive coverage of normal development, pathology, and professional issues, brand-new chapters highlight critical topics in assessment, diagnostic, and treatment, including: The role and prevalence of brain dysfunction in ADHD, conduct disorder, the autistic spectrum, and other childhood disorders. The neuropsychology of learning disabilities. Assessment of Spanish-speaking children and youth. Using the PASS (planning, attention, simultaneous, successive) theory in neurological assessment. Forensic child neuropsychology. Interventions for pediatric coma. With singular range, timeliness, and clarity, the newly updated Handbook of Clinical Child Neuropsycholgy reflects and addresses the ongoing concerns of practitioners as diverse as neuropsychologists, neurologists, clinical psychologists, pediatricians, and physical and speech-language therapists.